Her surprise Christmas courtship [large type] - Miller, Emma (Miller, Emma. Seven Amish Sisters, 2022)
Could following her heart...lead her to the man next door? Handsome Amish men like Elden Yoder don't fall for big girls like Millie Koffman, so she's sure he bid on her charity-auction cake by mistake. Only it's all part of Elden's plan to woo his pretty neighbor--and put his failed engagement behind him. But as the past threatens their new courtship, can they overcome their own insecurities...and find love for Christmas?